2015
DOI: 10.1186/s12916-015-0495-0
|View full text |Cite|
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis in BRIC countries: the cases of Brazil, Russia, India, and China

Abstract: Idiopathic pulmonary fibrosis (IPF), the prototype of interstitial lung diseases, has the worst prognosis and is the only interstitial lung disease for which approved pharmacological treatments are available. Despite being considered a rare disease, IPF patients pose major challenges to both physicians and healthcare systems. It is estimated that a large number of IPF patients reside in BRIC countries (Brazil, Russia, India, and China) given their overall total population of approximately 3 billion inhabitants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 28 publications
2
21
0
5
Order By: Relevance
“…5 A retrospective study in China revealed an increase in the number of ILD patients from 1.98% to 4.66% of all Chinese patients hospitalized for respiratory diseases between 1990 and 2003. 6 A similar trend was reported by another Chinese study which showed an increase in hospitalized ILD patients from 4.5% to 39.5% of all hospitalizations under the Department of Respiratory Diseases in 2003 and 2009, respectively. 7 This illustrates a gradual upward trend in the incidence of ILD in China over the years.…”
Section: Introductionsupporting
confidence: 83%
“…5 A retrospective study in China revealed an increase in the number of ILD patients from 1.98% to 4.66% of all Chinese patients hospitalized for respiratory diseases between 1990 and 2003. 6 A similar trend was reported by another Chinese study which showed an increase in hospitalized ILD patients from 4.5% to 39.5% of all hospitalizations under the Department of Respiratory Diseases in 2003 and 2009, respectively. 7 This illustrates a gradual upward trend in the incidence of ILD in China over the years.…”
Section: Introductionsupporting
confidence: 83%
“…Epidemiological data for IPF can vary widely due to variations in the data collection methods and classification terms used (table 1) [11,12]. Throughout Europe and North America, the estimated incidence of IPF has been reported to range between 2.8 and 19 cases per 100 000 people per year [23][24][25]. An analysis of national admissions data in Canada reported a higher rate of IPF than other national estimates, with an incidence rate of 18.7 per 100 000 cases and a broad prevalence of 41.8 per 100 000 cases, but noted that direct comparisons were not possible [26].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IPF increases with age, with the majority of patients aged >50 years at diagnosis and a higher proportion of males than females [6,25,26,28,29]. A regional observational study of ILD diagnoses performed by DUCHEMANN et al between January and December 2012 in Seine-Saint-Denis, a multi-ethnic county of Greater Paris in France, reported a prevalence rate for IPF of 8.2 per 100 000 [24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is likely that the burden of disease will be concentrated in the most densely populated region of the globe. BRIC countries (Brazil, Russia, India, and China), with an estimated 2.9 billion inhabitants, may comprise 2 million cases of IPF [98][99][100][101][102].…”
Section: Geoepidemiology Of Ipfmentioning
confidence: 99%